An alternative hypothesis to the widely held view that renal excretion of sodium accounts for resistance to salt-induced hypertension - Kurtz, Theodore W; DiCarlo, Stephen E; Pravenec, Michal; Schmidlin, Olga; Tanaka, Masae; Morris, R Curtis (Kidney international, 2016)
It is widely held that in response to high salt diets, normal individuals are acutely and chronically resistant to salt-induced hypertension because they rapidly excrete salt and retain little of it so that their blood volume, and therefore blood pressure, does not increase. Conversely, it is also widely held that salt-sensitive individuals develop salt-induced hypertension because of an impaired renal capacity to excrete salt that causes greater salt retention and blood volume expansion than that which occurs in normal salt-resistant individuals. Here we review results of both acute and chronic salt-loading studies that have compared salt-induced changes in sodium retention and blood volume between normal subjects (salt-resistant normotensive control subjects) and salt-sensitive subjects. The results of properly controlled studies strongly support an alternative view: during acute or chronic increases in salt intake, normal salt-resistant subjects undergo substantial salt retention and do not excrete salt more rapidly, retain less sodium, or undergo lesser blood volume expansion than do salt-sensitive subjects. These observations: (i) directly conflict with the widely held view that renal excretion of sodium accounts for resistance to salt-induced hypertension, and (ii) have implications for contemporary understanding of how various genetic, immunologic, and other factors determine acute and chronic blood pressure responses to high salt diets.
Keywords: salt-resistance; hypertenze; Sodium; Sodium Chloride, Dietary; sodium chloride; kuchyňská sůl; Blood Volume; lidé; krevní objem; salt-sensitivity; studie případů a kontrol; Hypertension; sodík; Case-Control Studies; sodium; salt; hypertension; blood pressure; kidney; Humans